Chromatin. Gene in der dritten Dimension - Thomas Seebeck (CHIMIA)
In the nuclei of eukaryotic cells, chromatin provides the structural framework for storage and processing of the genetic information. Biochemical analysis has revealed the presence of large amounts of a characteristic class of basic proteins, the histones, in association with DNA. Recent developments have lead to the concept of the nucleosome, a well defined complex of 8 histone molecules and 140 basepairs of DNA, as the structural building block of chromatin. The threads of nucleosomes can be wound into higher order structures, the solenoids. The continuous DNA molecule of each chromosome appears to be subdivided into many structural domains which are held together by a protein scaffold. While so far mostly information on the structure of transcriptionally inactive chromatin has been obtained, current research centers around the structural changes occurring upon activation of previously silent genes.